Fading-Aware Packet Scheduling Algorithm in OFDM-MIMO Systems. (24th May 2007) - Diao Diao, Zhifeng Zhifeng; Li Li, Victor O. K. Victor O. K.
Abstract : To maximize system throughput and guarantee the quality of service (QoS) of multimedia traffic in orthogonal frequency division multiplexing (OFDM) systems with smart antennas, a new packet scheduler is introduced to consider QoS requirements, packet location in the frame, and modulation level. In the frequency domain, several consecutive subchannels are grouped as a frequency subband. Each subband in a frame can be used to transmit a packet, and can be reused by several users in a multiple-input and multiple-output (MIMO) systems. In this paper, we consider the adaptive packet scheduling algorithms design for OFDM/SDMA system. Based on the BER requirements, all traffics are divided into classes. Based on such classification, a dynamic packet scheduler is proposed, which greatly improves system capacity, and can guarantee QoS requirements. Adaptive modulation is also applied in the scheduler. Then, the complexity analysis of these algorithms is given. When compared with existing schedulers, our scheduler achieves higher system capacity with much reduced complexity. The use of adaptive modulation further enhances the system capacity. Simulation results demonstrate that as the traffic load increases, the new scheduler has much better performance in system throughput, average delay, and packet loss rate.